Remarks at the 2020 Annual Meetings Press Conference, October 14, 2020 - Malpass, David (World Bank, Washington, DC, 2020)
World Bank Group President David Malpass spoke about the recession that has been deep, one of the deepest since the Great Depression. He announced about the Board approved the extension of the health emergency programs to up to twelve billion US dollars for vaccines and therapeutics and distribution of those in countries that don't otherwise have access. He mentioned that the moratorium was meant to address right away the fiscal gap that the poorest countries are experiencing. He explained the Debt Service Suspension Initiative (DSSI) itself simply defers debt payments and adds interest to them. He noted that World Bank plans to and provide extra support for social protection for the poorest in countries. He spoke about the need to have flexibility in economies, so that people can move to new jobs and positions, and the country can be prepared for a post-COVID global economy. He argued that it’s vital for the fragile states to recognize that women and girls make up a very productive half of the economy and need to be fully included in the legal structure and in the social fabric of the economies. He also mentioned ongoing work in Ecuador, Bangladesh, and Nigeria.